Technology and application of static drilling rooted geothermal energy pile - FANG Pengfei; ZHANG Rihong; LOU Yang; LIU Chunyang; PAN Weijie; ZHANG Qiushan; WANG Zhongjin; XIE Xinyu (Shenzhen Daxue xuebao. Ligong ban)
As a kind of building energy saving technology utilizing the shallow geothermal energy, energy pile is one of the ways to achieve the goal of reducing carbon emissions during building operation. Considering the shortcomings of construction technology for traditional energy pile, we propose the static drilling rooted geothermal energy pile (SDRGEP) and construction technology based on its characteristic. The short-term and long-term tests of SDREP are carried out by a test pile of a building in Ningbo. The variation properties of pile temperature, coefficient of performance (COP), thermally induced axial load and mobilized shaft resistance are analyzed. The test results show that the pile temperature gradually increases with time. COP value gradually decreases over time and then tends to be constant. Particularly, the performance of thermal axial stress and mobilized shaft resistance are determined by the constraint conditions of pile top and pile end. In the short-term test, the thermal axial stress shows the form of large in the middle and small in both ends, and there is a null point (NP). In the long-term test, the thermal axial stress at the top of the pile are larger. The mobilized shaft resistance is related to the time, temperature and constraint conditions, etc. It is varied gradually from one NP to three NPs along the pile. Therefore, the test results are related to the service state and construction technology of pile, which provides the theoretical basis for promoting the application of the SDRGEP.